2020
DOI: 10.1186/s10195-020-00551-x
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental knee arthroplasty, an enigma, and the ten enigmas of medial UKA

Abstract: Unicompartmental knee arthroplasty (UKA) is a bone-and ligament-sparing alternative to total knee arthroplasty in the patients with end-stage single-compartment degeneration of the knee. Despite being a successful procedure, the multiple advantages of UKA do not correlate with its usage, most likely due to the concerns regarding prosthesis survivability, patient selection, ideal bearing design, and judicious use of advanced technology among many others. Therefore, the purpose of this study is to review and sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 181 publications
(278 reference statements)
2
30
1
Order By: Relevance
“…Of note, a systematic review of 10 studies has reported good clinical outcomes with cementless UKA [71]. Nonetheless, we routinely use cemented prosthesis for all our knee arthroplasties, and this is supported by long-term studies [32,[72][73][74] and over a decade of successful results in our patients.…”
Section: Evidencementioning
confidence: 83%
“…Of note, a systematic review of 10 studies has reported good clinical outcomes with cementless UKA [71]. Nonetheless, we routinely use cemented prosthesis for all our knee arthroplasties, and this is supported by long-term studies [32,[72][73][74] and over a decade of successful results in our patients.…”
Section: Evidencementioning
confidence: 83%
“…Candidates for UKA have recently expanded to include younger and more active patients [21]. UKA is often compared with HTO [22][23][24], and the indications for surgery may also overlap. Although patients with severe varus alignment (HKA ≥ 185°) may be candidates for HTO, this study demonstrates that PROMs following Oxford UKA for knees with more than 5° of varus alignment were relatively good and not significantly different from those in the mild varus group.…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment line is conservative, mainly symptomatic, to delay joint replacement as long as possible [ 6 ]. Younger patients with mild OA tend to be dissatisfied after total knee arthroplasty (TKA) [ 7 , 8 ], and unicompartmental knee arthroplasty (UKA), in case of medial OA in a varus knee of an active patients, is still discussed but controversial in literature [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%